2001
DOI: 10.1016/s0008-6363(00)00245-5
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular irradiation with the liquid β-emitter Rhenium-188 to reduce restenosis after experimental wall injury

Abstract: Catheter transmitted endovascular irradiation with the liquid beta-emitter Rhenium-188 after vascular injury is feasible and effectively reduced neointimal hyperplasia in hypercholesterolemic rabbits. A significant reduction of the neointimal formation could be found already at a radiation absorbed dose of 15 Gy at the vessel surface. Following a surface dosage of 45 Gy the proliferative response to the vessel injury is almost completely abolished.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The major advantage of beta-irradiation is its low penetration depth, which minimizes the ionizing exposure of both the patient and the operator and decreases potential damage to the adjacent normal tissue. In coronary arteries, beta-irradiation has been shown to reduce neointimal formation in several animal experiments (17,18). Recently, two large randomized trials demonstrated that restenosis had been reduced by as much as 13.5% to 36% at the The Kruskal-Wallis test was used to evaluate the significant difference in the three study groups for proximal or distal portion in either 4weeks or 12-weeks follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The major advantage of beta-irradiation is its low penetration depth, which minimizes the ionizing exposure of both the patient and the operator and decreases potential damage to the adjacent normal tissue. In coronary arteries, beta-irradiation has been shown to reduce neointimal formation in several animal experiments (17,18). Recently, two large randomized trials demonstrated that restenosis had been reduced by as much as 13.5% to 36% at the The Kruskal-Wallis test was used to evaluate the significant difference in the three study groups for proximal or distal portion in either 4weeks or 12-weeks follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to directly image and assess the biodistribution and dosimetry of therapeutic radionuclides in vivo will assist in determining target specificity as well as validating the localization of dose over time. Currently, 188 Re-complexes have been used in bone pain palliation, stem cell transplantation, prevention of restenosis, treatment of fungal infections, and multiple cancers (19)(20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…One of the radioisotope candidates for the liquid-filled balloon approach is the ␤-emitting Re-188. Its application to intravascular brachytherapy has been evaluated in animal study 11,12 and clinical trial. 13 Dosimetry studies for Re-188 balloon source have been reported with Monte Carlo simulation.…”
Section: Introductionmentioning
confidence: 99%